Issues and Challenges faced by internal auditors of Private Sector Organizations - Chaudhary Abdul Rehman, Nisar Ahmad Bazmi Muqqadas Rehman (Social Science Learning Education Journal, 2016)
The purpose of this research article is gathered the views and perceptions of internal auditors working in private sector limited companies of Lahore city. An interview was conducted conveniently among 20 internal auditors of selected private sector companies of Lahore city. Data analysed thematically and in narrative form. Internal auditors narrated that they face a number of issues and challenges in their organizations. Results determine that due to lack of coordination of accounts staff, lack of management interest, Staff shortage, Ignoring rules and regulations while processing income and expenditures bills, staff union support to fraudsters and lack of awareness and training.